2022
DOI: 10.3390/jof8070739
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical Structure of Thermally Modified Spruce Wood Due to Decaying Fungi

Abstract: Fungi play a critical role in the decomposition of wood and wood-based products in use. The ability of decaying fungi to cause degradation of polysaccharides and lignin in the thermally modified Norway spruce (Picea abies L. Karst.) wood was examined with pure culture decomposition tests in laboratory conditions using the brown-rot fungus Serpula lacrymans (Schumacher ex Fries) S.F. Gray and white-rot fungus Trametes versicolor (Linnaeus ex Fries) Pilat. Spruce wood samples were primary thermally treated under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This interpretation is supported by abundant evidence that fire changes wood properties through heating and charring, which results in generally adverse effects on woody decomposition [144][145][146]. The heating-induced chemical changes of wood have been shown to lower moisture retention capacity [145,147], change wood chemical composition [144,145,[148][149][150] and lower nitrogen availability for decomposers [47,147,151]]. In response to these changes, fungi showed lower colonization rates and growth on affected wood, and the negative effects on fungal growth and wood decay generally increased with fire intensity as well as the duration of heating [144,145,148,152,153].…”
Section: Substrate Quality Influence On the Mtfmentioning
confidence: 80%
See 1 more Smart Citation
“…This interpretation is supported by abundant evidence that fire changes wood properties through heating and charring, which results in generally adverse effects on woody decomposition [144][145][146]. The heating-induced chemical changes of wood have been shown to lower moisture retention capacity [145,147], change wood chemical composition [144,145,[148][149][150] and lower nitrogen availability for decomposers [47,147,151]]. In response to these changes, fungi showed lower colonization rates and growth on affected wood, and the negative effects on fungal growth and wood decay generally increased with fire intensity as well as the duration of heating [144,145,148,152,153].…”
Section: Substrate Quality Influence On the Mtfmentioning
confidence: 80%
“…However, Figure 7 reveals that, all other factors being equal, the MTF response of DSTs killed by fire and mortality by other causes diverge markedly from a DBH of 25 cm, which might suggest that mechanical strength to resist breaking forces is more important than factors driving decomposition for DSTs killed by fire. This interpretation is supported by abundant evidence that fire changes wood properties through heating and charring, which results in generally adverse effects on woody decomposition [144][145][146]. The heating-induced chemical changes of wood have been shown to lower moisture retention capacity [145,147], change wood chemical composition [144,145,[148][149][150] and lower nitrogen availability for decomposers [47,147,151]].…”
Section: Substrate Quality Influence On the Mtfmentioning
confidence: 92%
“…The smallest changes occurred in the content of D-mannose and D-glucose. According to Vidholdová et al [ 78 ], the decrease in the content of saccharides of spruce wood is related to the action of wood fungi. For the further use of wood, it is important to know the degree of degradation of carbohydrates, because, for example, the content of glucomannan influences the strength properties of wood [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is also the possibility that the aluminum sulfate, being a thermal catalyst, had thermally modified the wood. It is reported that thermal treatment affects the chemical structure of the wood, mainly hemicellulose, which increases decay resistance [31]. This study did not investigate resistance to white rot fungi, as they are less common on softwoods, nor did it consider resistance to insects, which are less important in Canada.…”
Section: Discussionmentioning
confidence: 99%